A Confrontation of Two Concepts for the Description of the Over-capillary Moisture Range: Air Entrapment versus Low Capillarity. (November 2015) - Janssen, Hans; Vereecken, Evy; Holúbek, Matúš
Abstract: The reliable evaluation of moisture transfer in building materials is often crucial for the correct design of new structures or for the remediation of defective existing ones. An important condition in this respect is the accurate description of moisture storage and transport phenomena in building materials. Unfortunately, we are facing a dichotomy on that front, in relation to the over-capil- lary moisture range, more particularly the difference between capillary and saturated moisture content and the slow second phase in capillary absorption experiments. The widely accepted air entrapment paradigm explains these by presuming that air remains partially trapped in the pore system, escaping via dissolution into and diffusion through the pore water. The Delphin-adopted low capillarity approach on the other hand attributes these to low capillary forces counteracted by gravity in large pores. We therefore execute a series of measurements specifically targeting air entrapment versus low capillarity. In the first series, ca- pillary absorption tests are performed with water contact respectively at the bottom and the top surface of the sample, thus chang- ing the relative direction of gravity. The two variants should respectively give similar and unlike results in the air entrapment pa- radigm and low capillarity approach. In the second series, capillary absorption measurements are conducted at normal and reduc- ed air pressure, thus modifying the air content of the pore space. In the air entrapment paradigm and low capillarity approach res- pectively, the two variants should give rise to differing and matching results. Our experiments all demonstrate the validity of the widely accepted air entrapment paradigm, hence invalidating the Delphin-adopted low capillarity approach.